Prevalence and Factors Influencing the Preference of Traditional Bone Setting amongst Patients Attending Orthopaedic Clinics in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Traditional bone setting is a public health concern because of the late hospital presentation and resulting socioeconomic consequences.Aim:This study aimed to determine the prevalence and factors associated with preference of traditional bone setting among patients attending orthopedic clinics in Kano, Nigeria:Design:Descriptive cross-sectional design was used.Materials and Methods:Up to 370 patients were selected using a two-staged sampling technique.Statistical Analysis:Data were collected using interviewer administered questionnaires and analyzed using SPSS version 22.0 withP≤ 0.05 considered statistically significant.Results:The respondents age ranged 1 − 82 years with a median age of 29 (IQR = 20, 40) years. Majority of the patients (77.6%,n= 287) were older than 24 years of age with more than one-quarter (36.2%,n= 134) engaged in trading activities. Period prevalence (Within the last one year of visiting TBS) was 60.5% (95% CI: 55.4–65.6) while the point prevalence was 2.4% (95% CI: 1.1–4.6). Main reasons highlighted for the preference of traditional bone setting include low costs (8.6%,n= 32) and accessibility (6.5%,n= 24). Patients on admission had less probability of ever visited TBS (aOR: 0.4, 95% CI: 0.2–0.7), and patients with formal education were less likely to currently visit TBS (aOR: 5.0, 95% CI: 1.2–21.7)Conclusion:The prevalence of patronizing traditional bone setters is of significant public health concern despite the reported consequences. Therefore, the stakeholders should ensure regulated practices of the bone setters by providing them with appropriate guidelines including supervision of their practices.